Cryo-EM structure of PML RBCC dimer reveals CC-mediated octopus-like nuclear body assembly mechanism - Yangxia Tan; Jiawei Li; Shiyan Zhang; Yonglei Zhang; Zhiyi Zhuo; Xiaodan Ma; Yue Yin; Yanling Jiang; Yao Cong; Guoyu Meng (Cell Discovery)
Abstract Promyelocytic leukemia protein (PML) nuclear bodies (NBs) are essential in regulating tumor suppression, antiviral response, inflammation, metabolism, aging, and other important life processes. The re-assembly of PML NBs might lead to an ~100% cure of acute promyelocytic leukemia. However, until now, the molecular mechanism underpinning PML NB biogenesis remains elusive due to the lack of structural information. In this study, we present the cryo-electron microscopy (cryo-EM) structure of the PML dimer at an overall resolution of 5.3 Å, encompassing the RING, B-box1/2 and part of the coiled-coil (RBCC) domains. The integrated approach, combining crosslinking and mass spectrometry (XL-MS) and functional analyses, enabled us to observe a unique folding event within the RBCC domains. The RING and B-box1/2 domains fold around the α3 helix, and the α6 helix serves as a pivotal interface for PML dimerization. More importantly, further characterizations of the cryo-EM structure in conjugation with AlphaFold2 prediction, XL-MS, and NB formation assays, help unveil an unprecedented octopus-like mechanism in NB assembly, wherein each CC helix of a PML dimer (PML dimer A) interacts with a CC helix from a neighboring PML dimer (PML dimer B) in an anti-parallel configuration, ultimately leading to the formation of a 2 µm membrane-less subcellular organelle.